DESIGN AND DEVELOP AUGMENTED REALITY APPLICATION AS AN ANDROID-BASED INTERIOR DESIGN OFFER MEDIA - Rahmat Idhami; Amri; Aswandi (PT. Radja Intercontinental Publishing, 2023)
The use of augmented reality technology is increasing rapidly such as mobile android. This technology can be used as an interactive media offering, especially Interior Design offers. This study aims to determine the distance and angle and find out the differences in the application system in each application. Then this application will track and detect markers (markers) using the tracking system, after the marker is detected, a 3D object model appears above the marker as if the model were real. For this 3D model, the model must be made first using software. Applications are made using the markerless user defined target method and conducting tests on the utilization of this method using flat parameters, object shapes, distance, light and camera angles when tracking. The results of the test,